Respostas

2014-05-12T22:17:21-03:00
(2Y-1)² = (5-y)² 

(2y)² - 2.2y.1 + 1² = 5² - 2.5.y + y²

4y² - 4y + 1 = 25 - 10y + y² 

4y² - y² - 4y + 10y + 1 - 25 = 0

3y² + 6y - 24 = 0 (÷ 3)

y² + 2y - 8 = 0

Δ = b² - 4ac
Δ= 2² - 4.1.(-24)
Δ = 4 + 96
Δ = 100

y = -b  ₊/₋ √Δ
    -------------------
       2a

y = - 2 +/- √100
     ------------------
       2.1

y1 = (-2 + 10)/2 = 4

y2 = (-2 -10)/2 = -6



S = { -6, 4}
1 5 1
  • Usuário do Brainly
2014-05-12T22:30:24-03:00
(2y - 1)² = (5 - y)²
(2y - 1) . (2y - 1) = (5 - y) . (5 - y)
4y² - 2y - 2y + 1² = 5² - 5y - 5y + y²
4y² - 4y + 1 = 25 - 10y + y²
4y² - y² - 4y + 10y + 1 - 25 = 0
3y² + 6y - 24 = 0
Δ = b² - 4 . a . c
Δ = 6² - 4 . 3 . (- 24)
Δ = 36 + 288
Δ = 324

x = - b ± √Δ/2 . a
x = - 6 ± √324/2 . 3
x = - 6 ± 18/6

x' = - 6 + 18/6
x' = 12/6
x' = 2

x'' = - 6 - 18/6
x'' = - 24/6
x'' = - 4
muito obrigado amigo! MELHOR RESPOSTA